Communication Patterns in the Indonesian Ulema Council's Fatwa on the Law of Global Climate Change Control - Agus Fatuh Widoyo; Athoillah Islamy; Muhammad Abduh; Ariyadi Ariyadi (DAWUH : Islamic Communication Journal, 2026)
This study aims to identify the construction of mass communication functions in the literacy of the fatwa of the Indonesian Ulema Council (MUI) Number 86 of 2023 concerning the Law of Global Climate Change Control. This qualitative study uses a content analysis approach. Primary data using documents from the Indonesian Ulema Council (MUI) Fatwa Number 86 of 2023 on the Law of Global Climate Change Control, and various correlative scientific literature as secondary data. Harold Lasswell’s theory of mass communication as the foundation of the perspective. Documentation techniques were used in data collection, and data analysis techniques included reduction, presentation, and verification stages. This study concludes that there are three functions of mass communication in the literacy of MUI's fatwa on the Law of Global Climate Change Control, including the function of environmental monitoring related to the rampant phenomenon of natural disasters as a result of global climate change. Then, the function of social correlation related to the importance of cooperation between MUI with all elements of society and government agencies in the implementation of the fatwa on controlling global climate change. Furthermore, the function of social transmission is related to MUI's duty in instilling guidelines for Muslims in facing the problem of global climate change. This study highlights the importance of establishing a holistic approach to mass communication in disseminating fatwa-based literacy regarding environmental and socio-religious issues